Semi-Small Compressible Modules and Semi-Small Retractable Modules - Hashim Al Hakeem, Mohammed Baqer; Nuhad S. Al-Mothafar; Maryam Haghjooyan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let  be a commutative ring with 1 and  be left unitary  . In this paper we introduced and studied concept of semi-small compressible module (a     is said to be semi-small compressible module if  can be embedded in every nonzero semi-small submodule of . Equivalently,  is  semi-small compressible module if there exists a monomorphism  , ,     is said to be semi-small retractable module if  , for every non-zero  semi-small sub module in . Equivalently,  is semi-small retractable if there exists a homomorphism  whenever  .    In this paper we introduce and study the concept of semi-small compressible and semi-small retractable s as a generalization of compressible  and retractable  respectively and give some of their advantages characterizations and examples.